The Efficacy of e-Guru Application in Boosting Learning Effectiveness: Does It Deliver Results? - Ilham, Muhammad; Rahman, Fadhlur; Kholid, Mohammad; Sari, Dwhy Dinda (International Journal of Social Learning (IJSL), 2024)
In light of the unexpected events caused by the pandemic, educators urgently needed inventive educational resources to improve student comprehension. The rapid implementation of adaptable methods for instruction became necessary. E-guru is a user-friendly online platform that shows the potential to encourage student participation. This study conducted at State Vocational High School 1 of Tanah Luas in North Aceh examines the influence of e-guru on learning effectiveness. Using quantitative methods and conducting SPSS analysis, the results indicate no sie-guruchast impact of e-guru on effectiveness (p = 0.846 > 0.05). Based on the comparison between the T count value (0.196) and the T table value (1.685), the study concludes that e-guru does not significantly impact learning outcomes. The result emphasizes the necessity of further studies to enhance e-learning platforms to address evolving teaching and learning demands.